SOSIALISASI STRATEGI PENGALIHAN RISIKO MELALUI PERENCANAAN DANA ASURANSI SYARIAH PADA PENGEMUDI OJEK ONLINE - Ilda Alfiah; Rafika Rahmawati; Fajri Ryan Isnandar (An-Nizam, 2022)
Currently, there are still many people who cannot distinguish between Sharia Insurance and Conventional Insurance and some even do not know it at all even though insurance is very important for self-protection, especially in the current Pandemic Era. Therefore, this activity is carried out with the aim that the public can better know, understand, trust and apply sharia insurance as a good medium of self-protection. Then this paper was made with another purpose, namely as a report for the 2022 Real Work Lecture (KKN) organized by LPPM Islamic University "45" Bekasi. This paper uses qualitative research with the method of collecting library data and surveys through interviews. This Community Service Program was carried out well and was attended by 38 participants consisting of residents of the East Cikarang village, namely 11 online motorcycle taxi drivers and 27 Generation Z aged 19-24 years. The speaker at this webinar was filled by one of the Islamic banking lecturers at the Islamic University "45" Bekasi who is very experienced in the field of Sharia Insurance.